Development of a strategic plan for the sport of futsal in Iraq - Bachay Alshiblawi, Hasanain Hadi; Talebpour, Mahdi; Morteza Azimzadeh, Seyyed; Kashtidar, Mohammad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The purpose of this study was to develop a strategic plan for the sport of futsal in Iraq. This research is descriptive in nature. A qualitative study was conducted in the form of a survey. The sample of this study was composed of managers and experts of the Iraqi Ministry of Sports and the General Directorate of Sports of the Education Ministry, heads and vice presidents of Iraqi futsal, Iraqi futsal coaches, referees and elite athletes, and futsal veterans. The sample size for the present study was 23. The findings of the study revealed that Iraqi futsal has 16 strengths (S), 14 weaknesses (W), 14 opportunities (O) and 16 and threats (T). Considering these results, it is suggested that futsal in Iraq focuses more on strengths in the field of internal factors and try to solve the existing weaknesses